Step boundary conditions in the barotropic model - BUENDIA, E; VILLICANA, F; GALLEGOS, A; DELGADO, O; VALLE, EDEL (MAUSAM, 1988)
Step boundary conditions (SBC) are introduced and, jointly with a modified cyclicity condition have been implemented to a numerical model (based on the barotropic quasi-geostropic vorticlty equation) In order to restrict boundary effects and improve the weather forecasting skill for Region IV. Encouraging results were obtained which indicate that the cyclicity condition, although applicable, should be revised to produce even better short-range weather predictions.